The Descriptive Styles About Spring between Abu Tammam and Matsuo Basho: A Comparative Study - Ibnu Hudzaifah Hamka; Nursafira Lubis Safian (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2023)
Abu Tammam is considered a great Arab poet of his time. Abu Tammam created various poems from different topics such as spinning, praise, satire, and some of his poems include nature poetry about spring. On the other hand, Matsuo Basho was one of the most famous Japanese poets, but the greatest in writing haiku, and of most of his poetry about nature and its phenomena. Based on this, the researchers view that they should to be studied and analyzed the issue, and then compare the two poems of both poets.  The study aims to show their creativity in formulating the two poems, and to reveal the aspects of agreements and disagreement between their vision, using the descriptive analytical method before resorting to the American School approach in comparative study, where the study attempts to highlight on the similiarites and differences between the two studied poems. The study found that both poems are full of descriptive styles by the presence of plants and rain. However, the use of descriptive styles in the two poems differs from one poet to another. Where Matsuo Basho deals in his poetry with styles that refer to the signs of nature from the names of animals such as birdds, sparrows, butterflies, mice and bats, and these nouns were not found in Abu Tamam’s poem. While the names of the cosmic such as the sun, the moon and the earth combined more for description or similes and metaphor in Abu Tamam poem. These differences are due to the difference in culture, language, and geographical condition between the two studied literatures: Arabs and Japan.